EMPIRICAL VALIDATION OF OO METRICS IMPACT ON CHANGEABILITY - Dana CIUBĂNCAN; Paul ȚIRBAN (Studia Universitatis Babes-Bolyai: Series Informatica, 2020)
In the context of current software development, where changes to an application are made from one sprint to another, it’s more and more necessary for developers to be able to easily change the existing code. Starting from the existing literature and using two commercial projects with multiple versions and different architecture we are trying to confirm a correlation between a possible changeability indicator and variations of OO metrics. In our research we managed to provide empirical evidence of the relation between certain OO metrics that can be computed for a system and the changeability quality attribute.